Karya Patung Abstrak Lisa Widiarti Ditinjau Dari Bentuk Dan Medium - Khairun Nisa; Elvis Elvis; Armen Nazaruddin (Institut Seni Indonesia Padang Panjang, 2021)
This study discusses the form and medium used by Lisa Widiarti in making abstract sculptures. This study also briefly discusses Lisa Widiarti's short artistic journey. The discussion uses qualitative research methods, which include: observation, interviews, and literature study as well as research conducted in the city of Padang, West Sumatra. Based on the results of research on Lisa Widiarti's abstract sculpture, Lisa has produced dozens of abstract sculptures and almost every year always participates in exhibition events. Lisa tends to bring objects with the themes of love, social, everyday life, and beauty into her sculptures which are made with abstract shapes, and the mediums used in her work are various such as resin, stone, wood, cement, gypsum, metal plate and slurry. paper. Lisa is a female sculptor who is also a lecturer at Padang State University. Lisa is still able to survive with her abstract sculptures and become a resilient, creative, and active female sculptor in West Sumatra. Much can be learned andresearched from Lisa Widiarti's sculptures, especially abstract sculptures in terms of form and medium. It is hoped that research on Lisa Widiarti's abstract sculpture can be a reference so that there are opportunities for other researchers to research from a different scientific point of view.